Impact of Early Environment on Children's Mental Health: Lessons From DNA Methylation Studies With Monozygotic Twins. (26th November 2015) - Chiarella, Julian; Tremblay, Richard E.; Szyf, Moshe; Provençal, Nadine; Booij, Linda
Abstract : Over the past decade, epigenetic analyses have made important contributions to our understanding of healthy development and a wide variety of adverse conditions such as cancer and psychopathology. There is increasing evidence that DNA methylation is a mechanism by which environmental factors influence gene transcription and, ultimately, phenotype. However, differentiating the effects of the environment from those of genetics on DNA methylation profiles remains a significant challenge. Monozygotic (MZ) twin study designs are unique in their ability to control for genetic differences because each pair of MZ twins shares essentially the same genetic sequence with the exception of a small number of de novo mutations and copy number variations. Thus, differences within twin pairs in gene expression and phenotype, including behavior, can be attributed in the majority of cases to environmental effects rather than genetic influence. In this article, we review the literature showing how MZ twin designs can be used to study basic epigenetic principles, contributing to understanding the role of early in utero and postnatal environmental factors on the development of psychopathology. We also highlight the importance of initiating longitudinal and experimental studies with MZ twins during pregnancy. This approach is especially important to identify: (1) critical time periods during which the early environment can impact brain and mental health development, and (2) the specific mechanisms through which early environmental effects may be mediated. These studies may inform the optimum timing and design for early preventive interventions aimed at reducing risk for psychopathology.